Workers’ representations about risks at a chemical plant (Cadernos de Psicologia Social do Trabalho, 2002)
Occupational risk is a matter that has always been prominent in discussions about workers’ health and safety. It has been studied according to several theoretical approaches, some essentially “technicis” and others adopting a point of view that attributes special relevance to the social features. In the research presented here, the social approach was used to investigate workers’ representation of the risks they are exposed to in their professional activity. We sought to compare the representations of different groups of workers about two basic kinds of risk: accidents, which are more evident, and contamination by chemical products, which is less obvious to the layman. For this purpose a case study was carried out making use of the ethnographic approach in a large chemical plant, which is characterized by the presence of both kinds of risks. It was verified that access to technical information (which depends on the position occupied by the worker in the company structure) and the way that the relationship between company and workers is established (which is directly linked to the work organization) were the more relevant aspects in the construction of representations.